Comparisons of LES and RANS Computations with PIV Experiments on a Cylindrical Cavity Flow. (11th April 2013) - Su, Wen-Tao; Li, Xiao-Bin; Li, Feng-Chen; Wei, Xian-Zhu; Zheng, Zhi-Ying; Zhang, Xin
Abstract : A comparison study on the numerical computations by large eddy simulation (LES) and Reynolds-averaged Navier-Stokes (RANS) methods with experiment on a cylindrical cavity flow was conducted in this paper. Numerical simulations and particle image velocimetry (PIV) measurement were performed for two Reynolds numbers of the flow at a constant aspect ratio of H / R = 2.4 (R is the radius of the cylindrical cavity, and H is liquid level). The three components of velocity were extracted from 100 sequential PIV measured velocity frames with averaging, in order to illustrate the axial jet flow evolution and circulation distribution in the radial direction. The results show that LES can reproduce well the fine structure inside the swirling motions in both the meridional and the horizontal planes, as well as the distributions of velocity components and the circulation, in good agreement with experimental results, while the RANS method only provided a rough trend of inside vortex structure. Based on the analysis of velocity profiles at various locations, it indicates that LES is more suitable for predicting the complex flow characteristics inside complicated three-dimensional geometries.